1999
DOI: 10.1136/gut.44.4.552
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long term simvastatin administration as an adjunct to ursodeoxycholic acid: evidence for a synergistic effect on biliary bile acid composition but not on serum lipids in humans

Abstract: Background-Stimulated bile acid synthesis preferentially utilises newly synthesised cholesterol, raising the posssiblity that combination of simvastatin (an inhibitor of cholesterol synthesis) with ursodeoxycholic acid (UDCA; a stimulator of bile acid synthesis) may result in reduced bile acid synthesis and greater enrichment of the pool with UDCA than that achieved with UDCA treatment alone. Aims-To investigate the eVect of simvastatin and UDCA given alone and in combination on serum and biliary lipid and bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
(27 reference statements)
2
9
0
2
Order By: Relevance
“…[10], and Lanzarotto et al . [13] have shown that the addition of HMG CoA‐reductase inhibitors, lovastatin or simvastatin, to UDCA results in further reduction of cholesterol saturation: from 80% to 70% in healthy subjects and from 87% to 75% and 83% to 54% in patients with hypercholesterolaemia. The reduction of cholesterol saturation during treatment with UDCA was somewhat less pronounced in studies by Logan and Duane, Mazzella et al ., and Lanzarotto et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10], and Lanzarotto et al . [13] have shown that the addition of HMG CoA‐reductase inhibitors, lovastatin or simvastatin, to UDCA results in further reduction of cholesterol saturation: from 80% to 70% in healthy subjects and from 87% to 75% and 83% to 54% in patients with hypercholesterolaemia. The reduction of cholesterol saturation during treatment with UDCA was somewhat less pronounced in studies by Logan and Duane, Mazzella et al ., and Lanzarotto et al .…”
Section: Discussionmentioning
confidence: 99%
“…When cholesterol synthesis inhibitors (statins) were introduced as plasma lipid lowering agents in the 1980s it was hoped that this class of drugs would also result in dissolution of gallstones. Several studies have shown that the effect of statins on cholesterol saturation is limited [6–13]. With few exceptions, treatment with statins has not resulted in dissolution of cholesterol gallstones [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that statins, including simvastatin, show pleiotropic effects including anti‐inflammatory, antioxidant, and anti‐fibrotic effects as well as the ability to lower lipid levels. The anti‐fibrotic effects were demonstrated in non‐alcoholic steatohepatitis animal models by inhibition of HSC proliferation, induction of HSC senescence, suppression of collagen protein synthesis, and eventually reduction of hepatic fibrosis or carcinogenesis . The anti‐fibrotic function was demonstrated in lens epithelial cells and kidney tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Основанием для сомнений в способности УДХК потенцировать гиполипидемическое действие статинов являются результаты итальянского перекрестного ис-следования, более строгого в методическом отношении, хотя и меньшего по продолжительности и числу участ-ников, чем исследование РАКУРС [25]. В данном ис-следовании не удалось обнаружить преимуществ ком-бинированной терапии (симвастатин 10 мг/сут+УДХК 10 мг/кг/сут) перед монотерапией (симвастатин 10 мг/сут) по влиянию на липиды сыворотки крови [25].…”
Section: Statins and Ursodeoxycholic Acid статины и урсодезоксихолеваunclassified
“…В данном ис-следовании не удалось обнаружить преимуществ ком-бинированной терапии (симвастатин 10 мг/сут+УДХК 10 мг/кг/сут) перед монотерапией (симвастатин 10 мг/сут) по влиянию на липиды сыворотки крови [25]. Результаты небольшого испанского исследования, в ко-тором такие преимущества были выявлены [26], ма-лоубедительны ввиду серьезных методических нару-шений, допущенных при его проведении [27].…”
Section: Statins and Ursodeoxycholic Acid статины и урсодезоксихолеваunclassified